Disposition Effect: Brazilian Investors’ Behavior during the Covid-19 Pandemic - Pedro Lucas de Albuquerque Barreto; Claudio Henrique da Silveira Barbedo; Eduardo Camilo-da-Silva (BBR: Brazilian Business Review)
This study investigates the disposition effect with regard to Brazilian investors, with focus on the year 2020. The database is composed by more than 12,000 trades by 274 investors. We follow the method of Odean (1998) to estimate the proportions of gains and losses realized and test the null hypothesis of equality of these proportions in each portfolio. The results suggest that Brazilian investors behave in line with the disposition effect. They sell winning stocks too early and hold losing stocks too long. A stock that is gaining value is more likely to be sold from day to day compared to a stock that is losing value. The disposition effect was not found in March, which suggests that investors employed a loss-limit during periods of market stress, no matter if the stock went up or down.